The Role of Family Support in Shaping Self-Concept of Students at SMPN 27 Malang - Hermawan, Salsabila Yuli Adys; Sari, Dyah Ayu Aprillia; Panuluh, Wika Ajeng Damar; Zen, Ella Faridati; Elisa, Dina (Universitas Negeri Malang, 2024)
Adolescence is a transitional period characterized by the search for identity, which forms part of selfconcept. The formation of self-concept is influenced by several factors, one of which is family support. The role of the family, particularly that of parents, significantly contributes to the self-concept of students. Lack of family support negatively impacts students' understanding of their self-concept. This study aims to: 1) analyze students' perceptions of their self-concept, and 2) explore the extent of self-concept in students with family support and those without it. The subjects of this study are two students. There are two sources of data in this research: primary data obtained from interviews with the subjects, and secondary data collected from observations and interviews with people around the subjects. The method used in this study is a case study. Data collection techniques include snowball sampling with interview and observation methods. Data were analyzed using the flow analysis approach. The results of the study indicate that family support influences students' selfconcept, including aspects such as interaction patterns, self-control, emotional regulation, and its impact on personal development. Keywords: family support; self-concept; family demands